Review of Sickle Cell Disease and Spinal Pathology. Issue 7 (October 2019) - Rudy, Hayeem L.; Yang, David; Nam, Andrew D.; Cho, Woojin
Study Design: Sickle cell disease (SCD) is a relatively common blood disorder that has profound implications on the musculoskeletal system and particularly the spine; however, there is a paucity of data in the literature discussing this important topic. Objectives: (1) To elucidate common spinal pathologies affecting patients with SCD, as well as the medical and surgical treatments available for these patients. (2) To discuss indications for surgical management of spinal complications of SCD and important for orthopedic surgeons when taking patients with SCD to the operating room. Methods: A narrative review of the literature was performed. Results: Patients with SCD have a significantly higher risk of developing spinal pathologies including vertebral osteomyelitis, compression fracture, vertebral vaso-occlusive crises, and osteoporosis, among others. In addition, patients with sickle cell disease are particularly susceptible to developing perioperative and post-operative complications including surgical site infection, implant malfunction, and vertebral body compression fracture. Postoperatively patients with SCD are prone to developing complications and adequate hydration is necessary in order to reduce complications of SCD. Conclusions: Several spinal pathologies may arise secondary to SCD and distinguishing these pathologies from one another may be challenging due to similarities in symptoms and inflammatory markers. Although most patients with SCD can benefit from conservative treatment involving rest, symptomatic therapy, antibiotic therapy, and/or orthosis, surgical intervention may be indicated in certain cases. It is preferable to avoid surgery in patients with SCD due to an increased risk of complications such as wound infection and vaso-occlusive crisis.